2021
DOI: 10.3390/catal11111371
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Catalyzed Valorization of Furanics: A Sustainable Bridge to Fuels and Chemicals

Abstract: The development of efficient biomass valorization is imperative for the future sustainable production of chemicals and fuels. Particularly, the last decade has witnessed the development of a plethora of effective and selective transformations of bio-based furanics using homogeneous organometallic catalysis under mild conditions. In this review, we describe some of the advances regarding the conversion of target furanics into value chemicals, monomers for high-performance polymers and materials, and pharmaceuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 235 publications
(266 reference statements)
0
19
0
Order By: Relevance
“…80 Furfural and HMF are bio-based renewable feedstocks, and their oxidation products are important for the implementation of future green chemical industry. 81,82 It was found that while in the presence of other pyridine-based pincer complexes furfural and HMF degraded to unidentifiable polymers, the acridine-based complexes selectively oxidized them with high yields (495%), while suppressing decomposition. Mechanistic experiments indicated that the employed aromatized complex is dearomatized in the initial step to generate complex 4, which subsequently catalyses the reaction.…”
Section: Deaminative Oxidation Of Amines To Acidsmentioning
confidence: 99%
“…80 Furfural and HMF are bio-based renewable feedstocks, and their oxidation products are important for the implementation of future green chemical industry. 81,82 It was found that while in the presence of other pyridine-based pincer complexes furfural and HMF degraded to unidentifiable polymers, the acridine-based complexes selectively oxidized them with high yields (495%), while suppressing decomposition. Mechanistic experiments indicated that the employed aromatized complex is dearomatized in the initial step to generate complex 4, which subsequently catalyses the reaction.…”
Section: Deaminative Oxidation Of Amines To Acidsmentioning
confidence: 99%
“…Biomass-derived renewable aldehydes, specifically, furfural and 5-hydroxymethyl furfural (HMF), represent important chemical feedstocks that are expected to be crucial in the coming years for the sustainable production of commodity chemicals. , For example, 2,5-furan­dicarboxylic acid (FDCA), which can be synthesized via the complete oxidation of HMF or from furfural via oxidation and carboxylation, is a chemical that can potentially replace terephthalic acid in polymer synthesis. Our group has recently reported molecular complexes that can catalyze the oxidation of furfural to furoic acid using alkaline water as the oxidant while liberating H 2 gas (Figure b) .…”
Section: Oxidation Of Aldehydes To Carboxylic Acids Using Watermentioning
confidence: 99%
“…Owing to the negative consequences of fossil fuel use, intensive research is ongoing, focusing on transitioning toward a renewable framework for fuel and materials production. Furfural and 5-hydroxymethyl furfural (HMF) are chemical feedstocks produced by hydrolysis of biomass waste. Because of their renewable nature, the synthesis of commodity chemicals from furfural and HMF has garnered increasing attention. Among many products obtainable from furfural and HMF, their oxidation products, furoic acid and furan dicarboxylic acid (FDCA), respectively, hold particular interest (Figure A). Furoic acid has many applications including plastic plasticizer, food preservative, pharmaceutical intermediate, and FDCA precursor, and has potential applications in optics technology because of its unique crystal properties, with large-scale synthesis plants operated by multiple companies. Similarly, FDCA is a promising renewable alternative to terephthalic acid for polymers synthesis .…”
Section: Introductionmentioning
confidence: 99%